Peranan Bukti Forensik dalam Pembuktian Tindak Pidana Pemalsuan Uang - Ishma Safira; Handar Subhandi Bakhtiar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The crime of counterfeiting counterfeit money often occurs in Indonesia. Various policies through laws and implementing regulations have been issued, but these crimes always occur. One of the processes of proving the crime of counterfeiting money is using forensic science, therefore, the author is interested in analyzing what is the role of forensic evidence in proving the crime of counterfeiting money? In this research, the type of research used is normative research using a conceptual approach (conceptual approach) and legislation (legislative approach) related to forensic science. The results of the research explain that forensic evidence plays an important role in the investigation process and ultimately the judge can determine what crime the defendant deserves, forensic evidence is one of the pieces of evidence that perfects previous or other evidence as explained in Article 184 Paragraph (1) of the Criminal Procedure Code and Article 187 letter c KUHAP. The author's suggestion from the conclusions obtained is that investigations into criminal cases of money counterfeiting should always use forensic laboratory tests to obtain accurate evidence.